Maastricht criteria targeting and credit growth: Empirical evidences for the new EU member states - Bogdan Gabriel Moinescu (Romanian Journal of Fiscal Policy (RJFP), 2012)
The study aims to investigate the impact of credit growth on the Maastricht criteria targeting process in the new member states of the European Union. The methodological framework is based on a two-compenent transmission mechanism represented by the output gap and the nonperforming loans. The empirical analysis consists of a set of simplified econometric models, built by panel estimates using annual data from 2000 to 2011. Statistical results revealed the existence of a reaction of long term interest rates to the developments in sovereign risk premium, determined, in turn, by the impact of the mutual reinforcing between lending rate and output gap on the loan portfolio quality dynamics. Strengthening prudential conduct of monetary policy with a conservative macro-prudential policy is a critical need for increased resilience of nominal convergence to exogenous shocks, given that containing the volatility of economic activity depends in a decisive way, on succeding to maintain credit growth levels close to economic growth potential.
Keywords: G01; G17; G21; G32; G33; 330; Maastricht criteria; Lending to private sector; Output gap; Nonperforming loans; Primary budget balance